Textile Wastewater Treatment - Perrin Akçakoca Kumbasar, E.; Ekmekci Körlü, Ayşegül (IntechOpen, 2016)
During the dyeing process, losses of colorants to the water sources can be toxic and mutagenic and also decreases light penetration and photosynthesis activity. In recent years, since textile industry can generate large volumes of effluents, textile wastewater treatments have received considerable attention. The aim of this book is to look into textile wastewater treatments shortly. It is designed for readers who study on textile dyeing effluent. I would like to record my sincere thanks to authors for their contributions.